Explaining fraud deviancy attenuation in the United Kingdom - Button, Mark (Crime, law and social change, 2015)
Fraud is one of the most costly crimes to society. There have been a number of studies documenting the low priority and resources allocated to fraud, but there has been little attempt to conceptualise the processes which lead to this. This paper develops a concept that is the antithesis to deviancy amplification, deviancy attenuation, to examine why the level of resources and interest in fraud are not commensurate with the size of the problem. The paper also develops two further reverse concepts to further explain attenuation: de-labelling and immoral phlegmatism. Empirical evidence is offered in the form of case studies, statistical and survey data to support the arguments presented. The paper also illustrates these arguments through the comparison of the response to benefits fraud in the United Kingdom, which can be considered the one exception amongst frauds where labelling, moral panics and deviancy amplification occurs; explained by some Marxist commentators as a consequence of it being a lower class crime actively pursued by the powerful.